2020
DOI: 10.7150/ijbs.41230
|View full text |Cite
|
Sign up to set email alerts
|

The CARM1-p300-c-Myc-Max (CPCM) transcriptional complex regulates the expression of CUL4A/4B and affects the stability of CRL4 E3 ligases in colorectal cancer

Abstract: The transcription factor c-Myc and two cullin family members CUL4A/4B function as oncogenes in colorectal cancer. Our recent publication reveals that c-Myc specifically activates the expression of CUL4A/4B through binding to their promoters. However, the underlying mechanism of how c-Myc actions in this process is still unknown. Using mass spectrometry and immunoprecipitation assays, we identified c-Myc formed a transcriptional complex with its partner Max (Myc-associated factor X), a histone acetyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
(89 reference statements)
1
16
0
Order By: Relevance
“…Six lysine residues in Myc are direct substrates of p300, and acetylated Myc could interact with promoter binding factors as Miz-1 effectively (Zhang et al, 2005). A recent study reported that p300 binds to c-Myc N-terminus and recruit co-activator-associated arginine methyltransferase 1 (CARM1), in which CARM1-p300-c-Myc-Max (CPCM) transcriptional complex controls the transcription of CUL4A/4B (Lu et al, 2020 indicating that this function is independent of TRRAP (Vervoorts et al, 2003).…”
Section: Camp-response-element-bindingmentioning
confidence: 99%
“…Six lysine residues in Myc are direct substrates of p300, and acetylated Myc could interact with promoter binding factors as Miz-1 effectively (Zhang et al, 2005). A recent study reported that p300 binds to c-Myc N-terminus and recruit co-activator-associated arginine methyltransferase 1 (CARM1), in which CARM1-p300-c-Myc-Max (CPCM) transcriptional complex controls the transcription of CUL4A/4B (Lu et al, 2020 indicating that this function is independent of TRRAP (Vervoorts et al, 2003).…”
Section: Camp-response-element-bindingmentioning
confidence: 99%
“…The c-MYC pathway also plays a key role in the maintenance of T cell function and metabolic reprogramming and is independent of the mTOR pathway. The physiological condition, in terms of the transcription levels of c-MYC, reflects tissue and cell growth status; tissues with high proliferation rates have high c-MYC transcription levels (Lu et al, 2020). Several studies have demonstrated that many types of tumors are characterized by high c-MYC expression levels; however, in the absence of other mutations, c-MYC overexpression alone is not sufficient for tumorigenic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The sources and growth conditions of seven CRC cell lines including HT29, HT55, HCT-15, HCT-116, HCA-24, SW620, and T84 were the same as described previously. [ 18 ] For short hairpin RNA (shRNA) transfection, two independent MISSION shRNA lentiviral transduction particles of SIX1 (#TRCN0000015235 and #TRCN0000015237) and EYA1 (#TRCN0000303462 and #TRCN0000315624) were purchased from Sigma-Aldrich (St. Louis, MO, USA). These particles and pLKO.1-puro (Control) were individually transfected with FuGene 6 (Roche Diagnostics Corp., Indianapolis, IN, USA, #E2691) into cells following the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The ChIP assay was carried out as described previously. [ 18 ] To elucidate, cells (1 × 10 8 ) were cross-linked with 1% formaldehyde for 12 min, followed by quenching with 0.125 mmol/L glycine for 10 min. After rinsing twice with PBS buffer, cells were sonicated 15 × 30 s on ice in 4 mL lysis buffer provided by the Millipore ChIP Assay Kit (Millipore, Burlington, MA, USA, #17295).…”
Section: Methodsmentioning
confidence: 99%